EMPOWERING MUSLIM GENERATION Z IN DIGITAL HALAL ENTREPRENEURSHIP: A VALUE-DRIVEN TRANSFORMATION THROUGH SOCIAL MEDIA - Syahida Syahida; Risnani Eka Rahmadanty; Amelia Ramadhani (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to identify and analyze the role of Muslim Generation Z in promoting the development of halal entrepreneurship through the utilization of social media as the primary platform for promotion, education, and transactions. This research employs a descriptive qualitative approach using a literature review method, gathering data from various relevant sources to gain a comprehensive understanding of the phenomenon under study. The findings indicate that Generation Z, as digital natives, actively utilize digital platforms such as Instagram, TikTok, Facebook, and WhatsApp to promote halal products, educate consumers, and facilitate online transactions. However, limited understanding of Sharia principles and suboptimal digital infrastructure remain significant challenges that need to be addressed. A holistic strategy is required to strengthen the role of Generation Z in halal entrepreneurship, which includes enhancing Sharia and digital literacy, developing a digital ecosystem aligned with Sharia principles, and fostering cross-sector collaboration among entrepreneurs, government, and educational institutions. This study offers a new perspective on the involvement of Muslim Generation Z in the halal entrepreneurship ecosystem through social media, a topic that has been rarely explored in depth. The focus on digitalization by young Muslims within a Sharia-compliant context represents a significant contribution to the literature on halal entrepreneurship in the digital transformation era.